Effects of Parental Involvement on Achievement for Students Who Attend School in Rural America - Thimothy Z. Keith; Patricia B. Keith; Kimberly J. Quirk; Ellen Cohen-Rosenthal; Bettina Franzese (Journal of Research in Rural Education, 1996)
The purpose ofthis study was to compare the levels and effects on achievement ofparental involvement for students in rural versus urban and suburban schools. Latent variable structural equation modeling was used to determine the effects ofrural versus urban or suburban residence on parental involvement and change in achievement from eighth to tenth grade, and to compare the relative effects ofparental involvement on achievement in rural versus nonrural schools. The results suggest that rural school attendance does not affect either parental involvement or change in achievement, and that parental involvement has the same effects on the achievement ofstudents in rural schools as in urban or suburban schools. The effect of parental involvement on achievement is small, but significant and important. The findings suggest that group programs and individual interventions designed to increase parental involvement, ifsuccessful, will be equally effective in increasing achievement in rural, urban, and suburban schools.